Síntese e estudos de sistemas de bioencapsulação associados a peptídeos antimicrobianos miméticos da toxina natural CcdB - Oliveira, Isabelle Cavalini de [UNESP] (2014)
The new technologies, like synthetic peptides, for the development new drugs is a promising in biotechnology. Peptides with antibiotic properties, from Intracellular toxins produced by systems of post-segregational killer (PSK) in bacteria such as CcdB are recent examples of this strategy. Promising results have been obtained with respect to inhibition of the activity of the bacterial enzyme DNA gyrase and topoisomerase IV by toxins antimicrobial peptide derivatives that can be seen through in vitro assays such as electrophoresis in agarose gel. However, drugs formed by peptide structures, based on bacterial toxins, have been shown serious problems in therapeutic application due to their poor solubility and low biological membrane permeabilization. The aim of this study is the development and enhancement of nanostructured systems (liposomes) that allows the encapsulation of analogues peptides based on CcdB toxin and its consequent bacterial translocation in the cytosol, allowing them to reach their cellular targets, which are bacterial enzymes DNA gyrase and topoisomerase IV. Liposomes of the SUV type (Small unilamellar vesicles) of 100 nm diameter were prepared by extrusion and evaporation technique by varying the chemical composition of their formulations.Thus, we evaluated the encapsulation efficiency of the peptides through techniques of high performance liquid chromatography (HPLC) and UV-Vis spectroscopy and fluorescence. After efficiency of encapsulation tests the liposomes containing the peptides have been tested for growth inhibition in a liquid medium to different bacterial species. The results showed that the efficiency values for the analog CdBSG-2 were between 62 and 75% and the CcdBET-2 analogue values were between 52 and 71% Furthermore, the results of bacterial growth inhibition tests showed liposomal system that is effective, to inhibit 82% of gram positive Staphylococcus aureus...